Bioactive Metabolites From Acid-Tolerant Fungi in a Thai Mangrove Sediment - Gao, Hai; Wang, Yanan; Luo, Qiao; Yang, Liyuan; He, Xingxing; Wu, Jun; Kachanuban, Konthorn; Wilaipun, Pongthep; Zhu, Weiming; Wang, Yi (Frontiers in Microbiology, 2021)
Despite being potentially useful extremophile resources, there have been few reports on acid-tolerant fungi and their bioactive metabolites. Acidophilic/aciduric fungi (n = 237) were isolated from Thai mangrove sediments in an acidic medium. Using fungal identification technology (including morphologic observation, chemical screening, and sequence comparisons) all the isolates were identified and 41 representative isolates were selected for analysis of the phylogenetic relationships (ITS rDNA, β-tubulin, calmodulin, and actin gene sequences). There were seven genera identified – Penicillium; Aspergillus; Talaromyces; Cladosporium; Allophoma; Alternaria; and Trichoderma – in four taxonomic orders of the phylum Ascomycota, and Penicillium, Aspergillus, and Talaromyces were the dominant genera. Acidity tolerance was evaluated and 95% of the isolates could grow under extremely acidic conditions (pH 2). Six strains were classed as acidophilic fungi that cannot survive under pH 7, all of which had an extraordinarily close genetic relationship and belonged to the genus Talaromyces. This is the first report on the acidophilic characteristics of this genus. The antimicrobial, anti-tumor, and antiviral activities of the fermentation extracts were evaluated. Nearly three-quarters of the extracts showed cytotoxic activity, while less than a quarter showed antimicrobial or anti-H1N1 activity. The typical aciduric fungus Penicillium oxalicum OUCMDZ-5207 showed similar growth but completely different chemical diversity at pH 3 and 7. The metabolites of OUCMDZ-5207 that were obtained only at pH 3 were identified as tetrahydroauroglaucin (1), flavoglaucin (2), and auroglaucin (3), among which auroglaucin showed strong selective inhibition of A549 cells with an IC50 value of 5.67 μM. These results suggest that acid stress can activate silent gene clusters to expand the diversity of secondary metabolites, and the bioprospecting of aciduric/acidophilic microorganism resources in Thai mangrove sediments may lead to the discovery of compounds with potential medicinal applications.